Environmentally relevant concentrations of triclosan modulate the brain proteome profile of Labeo catla - Das, Basanta Kumar; Chakraborty, Hirak Jyoti; Ghosh, Subhrajyoti; Ganguly, Satabdi; Adhikari, Anupam; Kumar, Vikash; Kumar Nag, Subir (Frontiers in Marine Science, 2025)
IntroductionThe presence and effect of triclosan (TCS), a non-antibiotic antimicrobial biocide mostly used in personal, household, and healthcare products, on aquatic life is alarming nowadays. Although several studies have addressed TCS toxicity in aquatic organisms, its effects on brain tissues remain poorly explored.MethodsIn our study, label-free proteomics liquid chromatography- tandem mass spectrometry (LC–MS/MS) was used to analyze the long-term effects of TCS on the brain tissues of Labeo catla. Catla fingerlings (mean weight 12 ± 1.76 g; mean length 12 ± 2.14 cm) were exposed to TCS at 0.073 mg/L, a sublethal concentration corresponding to 1/10th of LC50 and within reported environmental hotspots, for 30 days in 50-L glass tanks with predefined laboratory conditions. After TCS exposure, fish brain tissue samples were collected and used for LC-MS/MS analysis.ResultsThe proteomic analysis suggested that TCS treatment of Catla brain tissues upregulated the proteins related to motor activity, neuron development, and semaphorin complex. In contrast, proteins related to myotube development, meiotic chromosome separation, myosin complex, and plasma membrane were downregulated. Principal component analysis (PCA) revealed significant proteomic alterations. ECT2 and Zcchc11 proteins showed marked upregulation, while EIF4G3B and PBRM1 were significantly downregulated. These results indicate that exposure to triclosan alters critical cellular growth pathways, RNA processing, and translation.DiscussionOur findings provide valuable insights into the molecular impact of environmental contaminants on aquatic species. Altered proteins (e.g., actin alpha1a/1b, myosin heavy chain fast skeletal muscle, camsap1b, and plexin B1) were consistently identified as potential candidate biomarkers of TCS neurotoxicity, pending further validation. Overall, our findings highlight the eco-physiological risks of TCS exposure, suggesting that proteomic disruptions in neuronal and muscular processes may translate into impaired fish fitness in contaminated habitats.